2022
DOI: 10.1111/opn.12447
|View full text |Cite
|
Sign up to set email alerts
|

Chronic wounds in persons living with dementia: An integrative review

Abstract: Background: Persons living with dementia (PLWD) are at risk for chronic wounds; however, they are rarely included in research.Objectives: To inform practice and research directions, the aim of this integrative review was to identify and synthesise previous knowledge about the characteristics of chronic wounds in PLWD, in terms of chronic wound types, prevalence, setting and interventions.Design: A literature search was conducted for publications in English using PubMed, Web of Science and CINAHL. The minimum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…These individuals had their cameras turned off and did not contribute to the discussion and were therefore excluded from the analysis. Similar issues in qualitative research have been reported in the literature [34][35][36][37]. All subsequent participants had a video screening call with the lead investigator (SM) prior to taking part to ensure they were eligible and able to meaningfully contribute to the FGD.…”
Section: Methodsmentioning
confidence: 86%
“…These individuals had their cameras turned off and did not contribute to the discussion and were therefore excluded from the analysis. Similar issues in qualitative research have been reported in the literature [34][35][36][37]. All subsequent participants had a video screening call with the lead investigator (SM) prior to taking part to ensure they were eligible and able to meaningfully contribute to the FGD.…”
Section: Methodsmentioning
confidence: 86%